ANOVA OPTIMIZATION OF DRILL BIT TEMPERATURE IN DRILLING OF PURE AND CARBON BLACK REINFORCED HIGH DENSITY POLYETHYLENE - ALPER UYSAL (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2019)
High density polyethylene materials have many application areas in automotive, aviation, electrical and electronic etc. industries. In some applications, their mechanical properties need to be improved. For this reason, some particles such as carbon black, graphite, carbon nanotubes, carbon fibers etc. were added to the polymer matrix. Although these types of material can be manufactured in near net shape, some machining operations such as drilling need to be performed. In this study, the drill bit temperatures in drilling of pure and carbon black reinforced high density polyethylene (HDPE) were optimized by using ANOVA (analysis of variance) statistical method.